Analysis of The Seventh Grade Students' Ability at SMP YPK Merauke in Solving Fraction Problems - Yosep Antonius Bhoy; Kamariah Kamariah; Markus Palobo (Riemann: Research of Mathematics and Mathematics Education, 2025)
This study aims to analyze the ability of seventh-grade students at SMP YPK Merauke in solving fraction problems. The research employed a descriptive quantitative approach involving 34 seventh-grade students as research subjects. The instrument used was a written test consisting of four essay-type questions designed to measure students’ ability to convert common fractions into mixed numbers, mixed numbers into common fractions, and common fractions into decimal forms. Data were analyzed by calculating the percentage of correct answers for each indicator and categorizing them according to students’ ability levels. The results showed that students’ ability to convert common fractions into mixed numbers was in the moderate category with a percentage of 44.11%. Students’ ability to convert mixed numbers into common fractions was in the good category with a percentage of 67.64%. Meanwhile, students’ ability to convert common fractions into decimals was very low, with percentages of 14.70% and 5.88%, respectively. These findings indicate that students tend to perform better on procedural problems than on problems requiring deep conceptual understanding. Therefore, mathematics instruction should emphasize conceptual understanding of fractions through the use of varied learning media and structured practice.